Araştırma temelli portfolyo çalışmasının yabancı dil öğretiminde okuma ve yazma becerisine, kelime edinimine ve araştırmaya yönelik tutuma etkileri - Ersin, Pınar (My University, 2005)
The general aim of the present study is to investigate the effects of a research-based portfolio study on reading and writing proficiency and vocabulary learning of Turkish upper-intermediate level EFL learners. The study specifically focuses on the learners' attitudes towards research. The following research questions are particularly addressed: 1. Will there be a difference between the learners who participate in a research-based portfolio study and those who do not participate in terms of their reading and writing proficiency? 2. Will there be a difference between the learners who participate in a research-based portfolio study and those who do not in terms of their vocabulary knowledge? 3. Will there be a change in the experimental group learners' attitudes towards research after they take part in the research-based portfolio study? Data were collected from 35 Turkish EFL learners, 18 forming the experimental and 17 the control group. The effects of the research-based portfolio study given to the experimental group for 6 weeks were tested via the progress achievement tests prepared and administered by the institution, pre- and post- checklists of target vocabulary items, and pre- and post-narratives written on what research meant by the experimental group learners. Findings of the progress achievement tests administered before and after the study indicated that both the experimental and the control group learners benefited from the instruction they received in terms of reading and writing proficiency. Another finding of the study revealed that the research-based portfolio study integrated into regular reading classes produced statistically significant differences in learners' knowledge of the target vocabulary items. Moreover, the research-based portfolio study integrated into regular reading classes helped learners look from a broader perspective towards research and the learners who were involved in the portfolio study developed an appreciation for conducting a research and learning for themselves. Hence, the results of the study indicated that a research-based portfolio study can be utilized as an effective tool in language learning classrooms to develop self-growth of the learners. KISA

Araştırma Temelli Portfolyo Çalışmasının Okuma ve Yazma Becerisine, Kelime Edinimine ve Araştırmaya Yönelik Tutuma Etkileri Pınar Ersin Bu çalışma, araştırma temelli portfolyo çalışmasının İngilizce'yi yabancı dil olarak öğrenen üst-düzey İngilizce seviyesine sahip Türk öğrencilerin okuma ve yazma becerilerine ve kelime edinimlerine etkisini ölçmeyi hedeflemektedir. Bu çalışma, portfolyo çalışmasının öğrencilerin araştırmaya yönelik tutumlarına etkisini araştırmayı amaçlamaktadır. Çalışma aşağıdaki soruları yanıtlamayı amaçlar: 1.Araştırma temelli portfolyo çalışmasına katılan öğrencilerle böyle bir çalışmaya katılmayan öğrencilerin okuma ve yazma becerileri başarıları açısından bir fark oluşacak mı? 2.Araştırma temelli portfolyo çalışmasına katılan öğrencilerle böyle bir çalışmaya katılmayan öğrenciler arasında kelime edinimleri açısından bir fark oluşacak mı? 3.Araştırma temelli portfolyo çalışması sonrasında, deney grubu öğrencilerinin araştırmaya yönelik sergiledikleri tutumlarında bir değişiklik oluşacak mı? Çalışmada kullanılan veriler, İngilizce'yi yabancı dil olarak öğrenen, 18'i deney, 17'si kontrol grubuna ait 35 Türk öğrenciden elde edilmiştir. Deney grubuna 6 hafta süreyle verilen araştırma temelli portfolyo çalışmasının etkileri, her iki gruba da uygulanan, çalışmanın başında ve sonunda verilen kurum tarafından hazırlanmış sınavlar, çalışmanın başında ve sonunda verilen kelime testi ve çalışmanın başında ve sonunda yalnızca deney grubu öğrencilerinin araştırmanın ne demek olduğuna dair yazdıkları kompozisyonlar ile ortaya çıkarılmıştır. Elde edilen bulgular, okuma dersi kapsamında gerçekleştirilen araştırma temelli portfolyo çalışmasının öğrencilerin okuma ve yazma becerilerini ve kelime edinimlerini arttırdığını göstermiştir. Araştırma sonucu elde edilen bulgulardan biri de, deney grubu öğrencilerinin araştırmaya yönelik tutumlarında meydana gelen olumlu yönde değişikliktir. Bunun yanında, araştırma temelli portfolyo çalışmasına tabi tutulan öğrenciler araştırma yapma, ve kendileri için öğrenme konularında bilinçlenmiştir. Sonuç olarak, araştırma temelli portfolyo çalışmasının yabancı dil sınıflarında etkin bir araç olarak kullanılabileceği kanıtlanmıştır.
Keywords: Dil; İngiliz Dili_Öğrenim ve Öğretim; İngilizce; Uygulamalı dilbilim